2012
DOI: 10.2174/1874357901206010049
|View full text |Cite
|
Sign up to set email alerts
|

Chronically HIV-1 Infected Patients Exhibit Low Frequencies of CD25+ Regulatory T Cells

Abstract: The characterization of regulatory T cells (Treg) during HIV infection has become of particular interest considering their potential role in the pathogenesis of the acquired immunodeficiency syndrome. Different reports on Tregs in HIV-infected patients vary greatly, depending on the state of disease progression, anatomical compartment, and the phenotypic markers used to define this cell subpopulation. To determine the frequency of Tregs we included paired samples from peripheral blood and rectal biopsies from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Similar to other studies [ 2 , 10 , 28 ], we observed increased frequencies of total CD4 + CD25 high CD127 low FoxP3 + Tregs in untreated HIV-infected individuals, which were normalized by early ART, while ECs showed lower Tregs frequencies than HIV-progressors and similar to uninfected individuals [ 18 , [72] , [73] , [74] , [75] ]. A distinctive differentiation pattern of Tregs was observed in acute HIV infection, which was characterized by higher proportions of naïve Tregs along with low frequencies of CM and EM Tregs, while in longitudinal analysis early ART initiation didn't affect these subsets.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other studies [ 2 , 10 , 28 ], we observed increased frequencies of total CD4 + CD25 high CD127 low FoxP3 + Tregs in untreated HIV-infected individuals, which were normalized by early ART, while ECs showed lower Tregs frequencies than HIV-progressors and similar to uninfected individuals [ 18 , [72] , [73] , [74] , [75] ]. A distinctive differentiation pattern of Tregs was observed in acute HIV infection, which was characterized by higher proportions of naïve Tregs along with low frequencies of CM and EM Tregs, while in longitudinal analysis early ART initiation didn't affect these subsets.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the detection of Treg as CD4 + CD25 + CD127 Low/− resulted in a lower percentage compared with the other two strategies (Fig. 2A), as previously described [24]. We therefore used CD4 + FOXP3 + CD127 Low/− as the Treg definition throughout the study.…”
Section: Resultsmentioning
confidence: 83%
“…In contrast in chronic HIV-infected donors, Treg might disrupt the development of efficient effector immune responses; in fact, in vitro depletion of CD4 + CD25 + T-cells from PBMC results in increased anti-HIV T-cell responses [16][18]. Accumulation of Treg in lymphoid tissues such as tonsils, lymph nodes and gut has been reported in untreated chronic progressors [19][24]. In patients with both immunological and virological responses to HAART, Treg frequency decreased in both rectal tissues and peripheral blood while CD4 + counts, Th17 and polyfunctional HIV-specific T-cell responses all increased in the gut [19], [20], [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…Treg cells seems to be a major contributor to the immune activation observed during chronic HIV infection, since a strong relationship between Treg cells depletion and CD4 + T cell activation was observed [ 38 , 39 ]. It is important to carefully observe that, in chronic HIV infection, a gradual increase of Treg cells (in terms of percentage) and a decrease of its absolute numbers, during progression of the disease, have already been described [ 39 43 ]. The opposite results regarding Treg cells relative and absolute frequencies are related to the fact that these cells are preferentially preserved compared to conventional CD4 + T cells [ 30 ].…”
Section: The Role Of Treg Cells On Hiv Infectionmentioning
confidence: 99%